The Sensory Components of High-Capacity Iconic Memory and Visual Working Memory - Bradley, Claire; Pearson, Joel (Frontiers in Psychology, 2012)
Early visual memory can be split into two primary components: a high-capacity, short-lived iconic memory followed by a limited-capacity visual working memory that can last many seconds. Whereas a large number of studies have investigated visual working memory for low-level sensory features, much research on iconic memory has used more “high-level” alphanumeric stimuli such as letters or numbers. These two forms of memory are typically examined separately, despite an intrinsic overlap in their characteristics. Here, we used a purely sensory paradigm to examine visual short-term memory for 10 homogeneous items of 3 different visual features (colour, orientation and motion) across a range of durations from 0 to 6 seconds. We found that the amount of information stored in iconic memory is smaller for motion than for colour or orientation. Performance declined exponentially with longer storage durations and reached chance levels after ~2 seconds. Further experiments showed that performance for the 10 items at 1 second was contingent on unperturbed attentional resources. In addition, for orientation stimuli, performance was contingent on the location of stimuli in the visual field, especially for short cue delays. Overall, our results suggest a smooth transition between an automatic, high-capacity, feature-specific sensory-iconic memory and an effortful ‘lower-capacity’ visual working memory.